Multi-drug resistant Salmonella Typhi resistant to Ceftriaxone isolated in a Tertiary care Hospital - Kamran, Rubina; Razaq, Hira Abdul; Sabih, Fauzia; Shafique, Muhammad (International Journal of Pathology, 2018)
Enteric fever is a systemic infection caused by Salmonella typhi and Salmonella para-typhi A and B. It is a major cause of morbidity and mortality worldwide. Multi-drug resistant (MDR)S. typhihas been reported since 1997 rendering the primary anti-typhoidal drugs and the fluoroquinolones as no longer a choice for typhoid treatment, thus leaving Ceftriaxone as the mainstay for enteric fever treatment. There are reports of emerging resistance to Ceftriaxone from many Asian countries. We report the first case of Ceftriaxone ResistantS. typhi from Children hospital, PIMS.A four-and-a-half-year-old girl presented with fever, abdominal pain and loss of appetite for last one month. Systemic examination revealed abdominal tenderness and mild hepatomegaly. The Typhidot test was positive for IgM. Blood culture was initially done in BACTEC 9050,(Automated blood culture system by B.D.) and was positive after 24 hours’ incubation at 35oC. This sample was later sub culturedon Blood and MacConkey’sagarand showed S. typhi colonies which were further confirmed by api, (analytical profile index,byBiomeurex, Italy). Sensitivity was applied according to Kirby Bauer’s Disc diffusion method using CLSI 2016 guidelines,and the organism was found sensitive to only three drugs: Augmentin, Chloramphenicol and Imipenem. The patient was treated with Imipenem intravenously and recovered.MDRS. typhi is on the rise worldwide and effective surveillance methods need to be brought into action to curtail these resistance trends.